IFRS CONVERGENCE INVESTIGATION: CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN RELATION TO GOOD CORPORATE GOVERNANCE AND CORPORATE SIZE - Suhartono, Suhartono; Mawarni, Iga S; Wahyuni, Sri (PEOPLE: International Journal of Social Sciences, 2018)
This research aims to determine the factors that influence the level of Corporate Social Responsibility Disclosures after International Financial Reporting Standards convergence by testing the effect of Institutional Ownership, Public Ownership, Board of Independent Commissioner Size and Corporate Size on Corporate Social Responsibility Disclosures index. Sample used are mining sector companies that listed on Indonesia Stock Exchange for period 2013-2016. The sources of the data were taken from audited financial reports and annual reports and sample were 19 banks which taken by using purposive sampling. This research uses quantitative approach with multiple linier regression analysis. The results show that institutional ownership, public ownership and corporate size have a positive and significant effect on corporate social responsibility disclosures. There is no evidence to suggest that board of independent commissioner size have any effect on corporate social responsibility disclosures. The results simultaneously show that Institutional Ownership, Public Ownership, Board of Independent Commissioner Size and Corporate Size have an influence on Corporate Social Responsibility Disclosures.